2019
DOI: 10.1097/rli.0000000000000572
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Gadopiclenol and P846, 2 High-Relaxivity Macrocyclic Magnetic Resonance Contrast Agents Without Protein Binding, in a Rodent Model of Hepatic Metastases

Abstract: The aim of this study was to evaluate in vitro and in vivo the enhancement properties of experimental gadolinium (Gd)-based contrast agents (GBCAs) with different molecular weights and hydration numbers (P846 and gadopiclenol) compared with clinically approved low-molecular, extracellular agents (gadopentetate and gadoterate) at 9.4 T and to discuss influencing factors on r1 relaxivities. Methods and Materials: All experiments were performed with a 9.4 T animal scanner (Bruker, Germany). We performed relaxomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…The r1-relaxivities (37°C, pH 7.4) of gadoquatrane were determined in human plasma at 1.41 T (per Gd: 11.8 mM −1 ·s −1 corresponding to 47.2 mM −1 ·s −1 per molecule) and 3.0 T (per Gd: 10.5 mM −1 s −1 corresponding to 41.9 mM −1 s −1 per molecule) (Table 1). The r1-relaxivity of gadoquatrane in human plasma was more than 2-fold (8-fold per molecule) higher compared with established GBCAs 22,23 …”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The r1-relaxivities (37°C, pH 7.4) of gadoquatrane were determined in human plasma at 1.41 T (per Gd: 11.8 mM −1 ·s −1 corresponding to 47.2 mM −1 ·s −1 per molecule) and 3.0 T (per Gd: 10.5 mM −1 s −1 corresponding to 41.9 mM −1 s −1 per molecule) (Table 1). The r1-relaxivity of gadoquatrane in human plasma was more than 2-fold (8-fold per molecule) higher compared with established GBCAs 22,23 …”
Section: Resultsmentioning
confidence: 86%
“…The r1-relaxivity of gadoquatrane in human plasma was more than 2-fold (8-fold per molecule) higher compared with established GBCAs. 22 , 23 …”
Section: Resultsmentioning
confidence: 99%
“…Gadopiclenol is a new high relaxivity macrocyclic GBCA. Preclinical studies have shown that this new macrocyclic chelate injected at the same dose as currently approved GBCAs improves the contrast-to-noise ratio in tumors by a factor of 2 to 3, as demonstrated in rat models of liver tumors 39 or brain gliomas 40 . Phase 3 clinical trials have just been completed.…”
Section: Discussionmentioning
confidence: 98%
“…It was shown some time ago that lanthanide complexes of the heptadentate ligand PCTA (3,6,9,15-tetraazabicyclo[9.3.1]pentadeca-1(15),11,13-triene-3,6,9-triacetic acid), which contain a pyridine moiety fused to the cyclen ring, have surprisingly high kinetic inertness for a bishydrated chelate [ 55 ]. Both of these principles (pyridine fusion and sidearm substitution) were applied in the design of Gadopiclenol, a high relaxivity GBCA currently in human clinical trials [ 56 , 57 , 58 , 59 ] to achieve excellent kinetic stability. A 2- to 3-fold greater relaxivity enhancements compared with current GBCA were achieved through a combination of two coordinating water molecules and slower molecular motion [ 57 ].…”
Section: What Structural Features Govern Kinetic Inertness?mentioning
confidence: 99%